Fluorine-free flame-retardant master batch, preparation method and application
By using fluorine-free flame retardant masterbatches in polycarbonate materials, combined with silicone copolymerized PC resin, polyborosiloxane and porous materials, the problems of flame retardant and electrical properties of the material are solved, and efficient flame retardant and electrical properties are achieved.
Patent Information
- Application Number
- CN202510000474.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing polycarbonate materials have insufficient flame retardant performance in flame tests, and the mechanical and electrical properties will be lost after adding flame retardant, especially the low leakage trace index (CTI), which limits its application in electronic and electrical appliances and photovoltaic products.
Fluorine-free flame retardant masterbatch is used, which consists of silicone copolymer PC resin, polyborosiloxane, porous materials, antioxidants and lubricants. It is prepared through extrusion and granulation processes, and porous materials such as polyborosiloxane and diatomaceous earth are used to improve the CTI performance of the material.
While maintaining the heat and impact resistance of the material, the CTI value of polycarbonate materials is significantly improved and the electrical performance is improved. It is suitable for electronic and electrical appliances and outdoor photovoltaic products with high safety requirements.
Smart Images

Figure BDA0005224862960000121 
Figure BDA0005224862960000131
Abstract
Description
Technical Field
[0001] The invention relates to a flame retardant masterbatch for polycarbonate, and in particular to a fluorine-free flame retardant masterbatch, a preparation method and application thereof. Background Art
[0002] The currently commercially available polycarbonate is bisphenol A polycarbonate (PC for short). As a commonly used engineering plastic, PC has excellent impact resistance and transparency, good heat resistance, flame resistance and insulation, and is widely used in electronics, household appliances, automobiles, construction, health care, agriculture and other fields. There are aromatic units in the main chain of PC, which will produce 20-25wt% of charred residues during combustion, but its flame retardancy still needs to be improved to meet the requirements of transportation, electronics, construction, etc. In order to meet this challenge, many flame retardants have been developed, such as bromine, phosphorus, sulfur, silicon-containing and other compounds to improve the flame retardancy of PC.
[0003] The ideal flame-retardant PC not only performs well in small-scale and large-scale flame tests, but also does not lose mechanical properties. The formation of the carbon layer is the most important condensed phase mechanism that interferes with combustion. The carbon layer masks the surface of the polymer, thereby preventing heat transfer and flame spread. Therefore, promoting carbonization is an effective way to reduce heat and smoke generation. The key to forming a core-shell structure protective layer is to quickly form a porous structure with good thermal oxidation resistance on the top surface of the sample at the beginning of combustion. Therefore, how to improve the cross-linking rate and thermal oxidation resistance of the degradation products is the key to constructing an ideal protective layer. Organosilicon compounds as flame retardants can be divided into low molecular weight compounds and high molecular weight compounds, most of the latter are siloxane and polysiloxane derivatives. These compounds will release less toxic gases and work in the condensed phase by facilitating the formation of a silica layer. Polysiloxane flame retardants catalyze the isomerization of PC and Fries rearrangement, promoting carbonization formation. CN105670259 discloses a polyborosiloxane flame retardant, which is firstly prepared by reacting triethoxyborane, silicon tetrachloride, a metallocene catalyst and a co-catalyst to generate a borosiloxane intermediate, and then washing the hydrolysis product of the reaction of the polyborosiloxane intermediate with tetrachlorosilane and water to remove small molecules. The polyborosiloxane PC composite material can reach a V-0 grade of 1.6 mm, and the tensile properties, bending properties, impact properties and transparency of the composite material are not affected. However, the above work did not investigate the influence on the electrical properties of PC.
[0004] The carbon-forming property of PC materials results in a low relative tracking index (CTI). At present, outdoor photovoltaic and electrical products have increasingly higher requirements for electrical performance, which will limit their application in this industry. Adding phosphorus-containing flame retardants can effectively improve the CTI of PC. Patent CN109370190A uses phosphazene flame retardants to improve CTI performance. Although this solution has a smaller decrease in heat resistance than conventional phosphorus flame retardants, it still has reduced heat resistance and impact resistance, and the cost is relatively high.
[0005] Therefore, it is necessary to develop new flame retardant solutions that can ensure the heat resistance and impact resistance of the material and improve the CTI performance of PC materials. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a fluorine-free flame retardant masterbatch, a preparation method and an application thereof.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] Based on the first aspect of the present invention, a fluorine-free flame retardant masterbatch is first provided, which comprises the following components based on a total weight of 100%:
[0009] Siloxane copolymer PC resin A 60-85%,
[0010] Polyborosiloxane 10-30%,
[0011] Porous materials 2-6%,
[0012] Antioxidant 0.2-0.6%,
[0013] Lubricant 0.5-4%;
[0014] The porous material is one or more of metal oxides, metal nitrides, silicates, diatomaceous earth, and diatomaceous earth modified by a silane coupling agent.
[0015] In some preferred examples, the melt index of the siloxane copolymer PC resin A under the test conditions of 300° C. and 1.2 kg is 15-35 g / 10 min, preferably 15-30 g / 10 min, and more preferably 15-25 g / 10 min;
[0016] Preferably, in the siloxane copolymer PC resin A, the mass content of the siloxane copolymer unit is 4-10%, preferably 4-9%, more preferably 5-9%.
[0017] In some preferred examples, the porous material is diatomaceous earth modified by a silane coupling agent, wherein the mass ratio of the silane coupling agent to the diatomaceous earth is 1:(2-9), preferably 1:(2-8), and more preferably 1:(2-7.5);
[0018] Preferably, the silane coupling agent in the silane coupling agent-modified diatomaceous earth is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0019] In the present invention, polyborosiloxane can be prepared by referring to any existing public technology, such as "Wu Yanjin, Wu Mingjun, Li Meijiang. "Research Progress on Preparation and Application of Polyborosiloxane". Polymer Bulletin. 2 (2012): 5."
[0020] The following is a feasible example of preparing polyborosiloxane provided by the present invention:
[0021] Octamethylcyclotetrasiloxane (D4), boric acid, tetraethyl silicate and hydrochloric acid are dissolved in an organic solvent and stirred continuously. The mixture is heated at 60-75°C for reaction for 3-5 hours, then kept at 100-120°C for 2-3 hours, the solvent is removed by vacuum distillation, and the mixture is cooled to below 60°C and dried in vacuum to obtain a powdery solid product, i.e. polyborosiloxane.
[0022] Preferably, the mass ratio of octamethylcyclotetrasiloxane (D4), boric acid and tetraethyl silicate is 1:(0.05-0.55):(0.08-0.3);
[0023] Preferably, the hydrochloric acid is a hydrochloric acid solution with a concentration of 36.0-38.0%, and the amount of the hydrochloric acid solution is 10-30% of the total mass of the raw materials.
[0024] Preferably, the organic solvent is selected from one or more of diethylene glycol dimethyl ether, methyl tert-butyl ether, propylene glycol dimethyl ether and triethylene glycol dimethyl ether.
[0025] In the present invention, the introduction of polyborosiloxane not only brings considerable flame retardant properties to the PC material, but also surprisingly finds that the synergistic use of polyborosiloxane and porous materials such as diatomaceous earth can improve the CTI performance of the material without losing the impact resistance of the material, especially when used in conjunction with diatomaceous earth modified by a silane coupling agent within a certain proportion range, the obtained flame retardant masterbatch can significantly improve the CTI performance of the PC composition, and has broad application prospects in electronic appliances and outdoor photovoltaic products with high safety requirements.
[0026] Based on the second aspect of the present invention, there is also provided a method for preparing the fluorine-free flame retardant masterbatch as described above, comprising the following steps: fully mixing the siloxane copolymerized PC resin A, polyborosiloxane, porous material, antioxidant and lubricant, extruding and granulating to obtain the fluorine-free flame retardant masterbatch;
[0027] Preferably, the extrusion temperature is 245-270° C., and the extrusion speed is 100-200 rpm.
[0028] According to the third aspect of the present invention, a polycarbonate composition is also provided, which comprises the following components based on a total weight of 100%:
[0029] PC resin 68-90%,
[0030] Siloxane copolymer PC resin B 6-20%,
[0031] The fluorine-free flame retardant masterbatch in the present invention is 1.5-18%,
[0032] Antioxidant 0.2-0.6%,
[0033] Lubricant 0.5-2%.
[0034] Other additives 0-6%.
[0035] In some preferred examples, the PC resin has a melt index of 3-65 g / 10 min, preferably 5-65 g / 10 min, and more preferably 5-50 g / 10 min under the test conditions of 300° C. and 1.2 kg.
[0036] In some preferred examples, the melt index of the siloxane copolymer PC resin B under the test conditions of 300° C. and 1.2 kg is 0.1-5 g / 10 min, preferably 0.2-4 g / 10 min, and more preferably 0.2-3 g / 10 min;
[0037] Preferably, in the siloxane copolymer PC resin B, the mass content of the siloxane copolymer unit is 12-35%, preferably 12-32%, more preferably 15-30%.
[0038] In some preferred examples, the other auxiliary agents include any one or more of ultraviolet absorbers and toughening agents.
[0039] According to a fourth aspect of the present invention, there is also provided a method for preparing the polycarbonate composition as described above, comprising the following steps: fully mixing PC resin, siloxane copolymer PC resin B, the fluorine-free flame retardant masterbatch described above, antioxidant, lubricant, and other additives, extruding, and pelletizing to obtain a polycarbonate composition;
[0040] Preferably, the extrusion temperature is 250-300° C., and the extrusion speed is 150-400 rpm.
[0041] In the fluorine-free flame retardant masterbatch and polycarbonate composition provided by the above content of the present invention, the antioxidant can be selected from one or more of hindered phenols, phosphites, thioesters, benzofurans, acryl-modified phenols, and hydroxylamine antioxidants, including but not limited to one or more of 1076, 168, and PEP-36;
[0042] The lubricant can be selected from one or more of fatty alcohols, fatty acids, fatty acid esters, montanic acid and its derivatives, amide waxes, saturated hydrocarbons, polyolefin waxes and its derivatives, silicone and silicone lubricants, including but not limited to one or more of pentaerythritol stearate and montan wax 6901.
[0043] The ultraviolet absorber includes, but is not limited to, one or more of benzophenone, benzotriazole, triazine, benzoate, cyanoacrylate, and phenylimidazole ultraviolet absorbers.
[0044] The impact modifier includes, but is not limited to, one or more of styrene-butadiene-acrylonitrile copolymer (ABS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS), methyl methacrylate-butadiene-styrene copolymer (MBS), acrylate-styrene-acrylonitrile copolymer (ASA), methyl methacrylate-butadiene copolymer (MB), acrylonitrile-ethylene propylene rubber-styrene copolymer (AES), styrene-butadiene copolymer (SB), methyl methacrylate-acrylate copolymer (MA), and methyl methacrylate-acrylate-styrene copolymer (MAS).
[0045] According to the fifth aspect of the present invention, there is also provided an application of the polycarbonate composition as described above in electronic appliances and outdoor photovoltaic equipment.
[0046] The present invention uses polyborosiloxane and porous materials such as diatomaceous earth (especially diatomaceous earth modified by a silane coupling agent) in synergistic use to prepare a fluorine-free flame retardant masterbatch, which is then applied to a polycarbonate composition. The obtained PC composition material can not only maintain high heat resistance and impact resistance, but also greatly improve the CTI value, and has stable electrical properties, thus having broad application prospects. DETAILED DESCRIPTION
[0047] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0048] The main raw materials used in the following examples of the present invention are as follows. Unless otherwise specified, other raw materials are purchased from commercial sources.
[0049] PC resin (PC-1): CLARNATE 2100, melt index (300°C, 1.2kg) = 8.5 g / 10 min, Wanhua Chemical Group Co., Ltd.
[0050] PC resin (PC-2): CLARNATE 2220, melt index (300°C, 1.2kg) = 20g / 10min, Wanhua Chemical Group Co., Ltd.
[0051] PC resin (PC-3): CLARNATE 2350, melt index (300°C, 1.2kg) = 35g / 10min, Wanhua Chemical Group Co., Ltd.
[0052] Siloxane copolymer PC resin (Si-PC-A1): CLARNATE S2440, siloxane copolymer unit content of 7.5 wt%, melt index (300° C., 1.2 kg) = 20 g / 10 min, Wanhua Chemical Group Co., Ltd.
[0053] Siloxane copolymer PC resin (Si-PC-A2): CLARNATE S2340, siloxane copolymer unit content of 9 wt%, melt index (300° C., 1.2 kg) = 15 g / 10 min, Wanhua Chemical Group Co., Ltd.
[0054] Siloxane copolymer PC resin (Si-PC-A3): CLARNATE S2630, siloxane copolymer unit content of 5 wt%, melt index (300°C, 1.2 kg) = 32 g / 10 min, Wanhua Chemical Group Co., Ltd.
[0055] Siloxane copolymer PC resin (Si-PC-B1): CLARNATE S2060, siloxane copolymer unit content of 20 wt%, melt index (300° C., 1.2 kg) = 1.3 g / 10 min, Wanhua Chemical Group Co., Ltd.
[0056] Siloxane copolymer PC resin (Si-PC-B2): CLARNATE S2080, siloxane copolymer unit content of 30 wt%, melt index (300° C., 1.2 kg) = 0.4 g / 10 min, Wanhua Chemical Group Co., Ltd.
[0057] Lubricant (WAX-1): Pentaerythritol tetrastearate, Faji Chemicals (Zhangjiagang) Co., Ltd.
[0058] Antioxidant (AO-1): a composite antioxidant having a weight ratio of 4:1 between tris[2,4-di-tert-butylphenyl]phosphite and β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0059] Octamethylcyclotetrasiloxane (D4), 98.0%, Inno Chemical Technology Co., Ltd.
[0060] Boric acid (BA), Aladdin Industries (China).
[0061] Tetraethyl silicate (TEOS), Aladdin Industries (China).
[0062] Diethylene glycol dimethyl ether (99.5%), Shanghai Aladdin Biochemical Technology Co., Ltd.
[0063] Hydrochloric acid (HCl, 36.0-38.0%), Wanhua Chemical Group Co., Ltd.
[0064] Diatomaceous earth-R, unmodified diatomaceous earth, Sinopharm Chemical Reagent Co., Ltd.
[0065] γ-Glycidyloxypropyltrimethoxysilane, commercially available.
[0066] Distearoyloxyisopropylaluminate, commercially available.
[0067] The performance testing methods mainly adopted in the following embodiments of the present invention are as follows:
[0068] (1) Izod notched impact strength: At 23°C, a 4.0 mm thick injection molded cantilever beam test specimen was used. A notch machine was used to prepare a 2.0 mm deep notch. The notched cantilever impact strength was measured according to GB / T1043.1-2008. The notched cantilever impact strength was expressed in kJ / m 2 Record the results.
[0069] (2) Heat Deformation Temperature: Tested at 23°C in accordance with ISO 75 standard and the results are recorded in °C.
[0070] (3) Flame retardant test: Two types of specimens, 127*12.7*3.0 mm and 127*12.7*1.5 mm, and a specimen with a specification of 150*150*3.0 mm, were injection molded. Pretreatment and flame retardant properties were performed according to UL94 standard, and the results were recorded as V0, V1, V2, HB, 5VB, and 5VA.
[0071] (4) Comparative tracking index test: Prepare a 90*80*3.0 mm sample and test the comparative tracking index (CTI) of the sample according to the IEC60112 standard, and record the result in V. The higher the CTI, the better the electrical performance.
[0072]
Preparation Example 1
[0073] 23.73 g of D4, 1.24 g of boric acid, 2.08 g of TEOS and 3 ml of hydrochloric acid were dissolved in 100 ml of diethylene glycol dimethyl ether, heated to 70°C for 4 hours under magnetic stirring, and then kept at 120°C for 2 hours. The solvent was removed by reduced pressure distillation, and then vacuum dried at 60°C to obtain a powdery solid product polyborosiloxane, recorded as PBS-1.
[0074] 14.83 g of D4, 3.09 g of boric acid, 2.08 g of TEOS and 4 ml of hydrochloric acid were dissolved in 100 ml of diethylene glycol dimethyl ether, heated to 65°C for 4 hours under magnetic stirring, and then kept at 110°C for 2 hours. The solvent was removed by reduced pressure distillation, and then vacuum dried at 60°C to obtain a powdery solid product polyborosiloxane, recorded as PBS-2.
[0075] 8.90 g of D4, 4.64 g of boric acid, 2.08 g of TEOS and 4 ml of hydrochloric acid were dissolved in 100 ml of diethylene glycol dimethyl ether, heated to 60° C. for 4 hours under magnetic stirring, and then kept at 100° C. for 2 hours. The solvent was removed by reduced pressure distillation, and then vacuum dried at 60° C. to obtain a powdery solid product polyborosiloxane, recorded as PBS-3.
[0076]
Preparation Example 2
[0077] 100 g of diatomaceous earth-R was added to 1 L of ethanol aqueous solution with a mass concentration of 40%, and the mixture was ultrasonically dispersed for 40 min. Then, acetic acid was added under magnetic stirring (speed 350 r / min) to adjust the pH to 5.1, and 25 g of γ-glycidyloxypropyltrimethoxysilane was added. The temperature was raised to 75°C and the stirring reaction was continued for 5 h. After the reaction was completed, the mixture was allowed to stand and cool, filtered, washed 3 times with ethanol, and dried in vacuo at 60°C to obtain modified diatomaceous earth-M1.
[0078] 50 g of diatomaceous earth-R was added to 1 L of ethanol aqueous solution with a mass concentration of 40%, and the mixture was ultrasonically dispersed for 40 min. Then, acetic acid was added under magnetic stirring (speed 350 r / min) to adjust the pH to 5.1, and 25 g of γ-aminopropyltriethoxysilane was added. The temperature was raised to 75°C and the stirring reaction was continued for 5 h. After the reaction was completed, the mixture was allowed to stand and cool, filtered, washed 3 times with ethanol, and dried in a vacuum at 60°C to obtain modified diatomaceous earth-M2.
[0079] 200 g of diatomaceous earth-R was added to 1 L of ethanol aqueous solution with a mass concentration of 40%, and the mixture was ultrasonically dispersed for 40 min. Then, acetic acid was added under magnetic stirring (speed 350 r / min) to adjust the pH to 5.1, and 25 g of γ-methacryloxypropyltrimethoxysilane was added. The temperature was raised to 75°C and the stirring reaction was continued for 5 h. After the reaction was completed, the mixture was allowed to stand and cool, filtered, washed 3 times with ethanol, and dried in vacuo at 60°C to obtain modified diatomaceous earth-M3.
[0080] 100 g of diatomaceous earth-R was added to 1 L of ethanol aqueous solution with a mass concentration of 40%, and the mixture was ultrasonically dispersed for 40 min. Then, acetic acid was added under magnetic stirring (speed 350 r / min) to adjust the pH to 5.1, and 15 g of γ-glycidyloxypropyltrimethoxysilane was added. The temperature was raised to 75°C and the stirring reaction was continued for 5 h. After the reaction was completed, the mixture was allowed to stand and cool, filtered, washed 3 times with ethanol, and dried in vacuo at 60°C to obtain modified diatomaceous earth-M4.
[0081] 100 g of diatomaceous earth-R was added to 1 L of ethanol aqueous solution with a mass concentration of 40%, and the mixture was ultrasonically dispersed for 40 min. Then, acetic acid was added under magnetic stirring (speed 350 r / min) to adjust the pH to 5.1, and 25 g of distearyloxyisopropylaluminate was added. The temperature was raised to 75°C and the stirring reaction was continued for 5 h. After the reaction was completed, the mixture was allowed to stand and cool, filtered, washed 3 times with ethanol, and dried in vacuo at 60°C to obtain modified diatomaceous earth-D1.
[0082] [Example 1]
[0083] The fluorine-free flame retardant masterbatch was prepared as follows:
[0084] 1.687kg Si-PC-A1, 0.2kg PBS-1, 0.08kg modified diatomaceous earth-M1, 0.003kg AO-1 and 0.03kg WAX-1 were mixed using a powder grinder, and then the mixture was added to a Buss mixer for extrusion and granulation at an extrusion temperature of 245-270°C and a rotation speed of 200rpm to obtain a fluorine-free flame retardant masterbatch PBSMB-1.
[0085] [Example 2]
[0086] The fluorine-free flame retardant masterbatch was prepared as follows:
[0087] 1.507kg Si-PC-A2, 0.4kg PBS-2, 0.06kg modified diatomaceous earth-M2, 0.003kg AO-1 and 0.03kg WAX-1 were mixed using a powder grinder, and then the mixture was added to a Buss mixer for extrusion and granulation at an extrusion temperature of 245-270°C and a rotation speed of 150rpm to obtain a fluorine-free flame retardant masterbatch PBSMB-2.
[0088] [Example 3]
[0089] 1.247kg Si-PC-A3, 0.6kg PBS-3, 0.12kg modified diatomaceous earth-M3, 0.003kg AO-1 and 0.03kg WAX-1 were mixed using MIXACO, and then the mixture was added to a Buss mixer for extrusion and granulation at an extrusion temperature of 245-270°C and a rotation speed of 100rpm to obtain a fluorine-free flame retardant masterbatch PBSMB-3.
[0090] [Example 4]
[0091] The fluorine-free flame retardant masterbatch PBSMB-4 was prepared according to the formula and method basically the same as that of Example 1, except that the modified diatomaceous earth-M1 was replaced by an equal amount of modified diatomaceous earth-M4.
[0092] [Comparative Example 1]
[0093] The fluorine-free flame retardant masterbatch PBSMB-5 was prepared according to the formula and method basically the same as that of Example 1, except that the modified diatomaceous earth-M1 was replaced by an equal amount of modified diatomaceous earth-D1.
[0094] [Comparative Example 2]
[0095] The fluorine-free flame retardant masterbatch PBSMB-6 was prepared according to the formula and method basically the same as that of Example 1, except that the modified diatomaceous earth-M1 was replaced by an equal amount of diatomaceous earth-R.
[0096] [Comparative Example 3]
[0097] The fluorine-free flame retardant masterbatch PBSMB-7 was prepared according to the formula and method basically the same as that of Example 1, except that the modified diatomaceous earth-M1 was not added.
[0098]
Application example 1-6
[0099] Referring to the formula in Table 1, the raw materials were mixed respectively and melt-kneaded using a Coperion STS-35 twin-screw extruder. The processing temperature was 230° C. for zone 1, 260° C. for zone 2, 285° C. for zone 3, 280° C. for zone 4, 275° C. for zones 5 to 9, and 280° C. for the die. After extrusion, pelletization was performed to obtain the polycarbonate compositions in each application example.
[0100] Table 1. Formulation of polycarbonate composition in Application Examples 1-6
[0101]
[0102]
Comparative Application Example 1
[0103] A polycarbonate composition was prepared according to the method in Application Example 1, except that the fluorine-free flame retardant masterbatch PBSMB-1 was replaced with an equal amount of PBSMB-5.
[0104]
Comparative Application Example 2
[0105] A polycarbonate composition was prepared according to the method in Application Example 1, except that the fluorine-free flame retardant masterbatch PBSMB-1 was replaced with an equal amount of PBSMB-6.
[0106]
Comparative Application Example 3
[0107] A polycarbonate composition was prepared according to the method in Application Example 1, except that the fluorine-free flame retardant masterbatch PBSMB-1 was replaced with an equal amount of PBSMB-7.
[0108]
Comparative Application Example 4
[0109] The polycarbonate composition was prepared according to the method in Application Example 1, except that the fluorine-free flame retardant masterbatch PBSMB-1 was not added.
[0110] The polycarbonate compositions obtained in the above application examples and comparative application examples were subjected to the performance tests shown in Table 2, and the results are as follows.
[0111] Table 2. Performance test results
[0112]
[0113] The experimental results in Table 2 show that the polycarbonate composition prepared by using the fluorine-free flame retardant masterbatch provided by the scheme of the present invention has excellent flame retardant properties and significantly improved CTI value, and the mechanical properties of the material are maintained well, which has significant advantages over the scheme in the comparative application example.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A fluorine-free flame retardant masterbatch, characterized in that: Based on the total weight of 100%, it contains the following components: Siloxane copolymer PC resin A 60-85%, Polyborosiloxane 10-30%, Porous materials 2-6%, Antioxidant 0.2-0.6%, Lubricant 0.5-4%; The porous material is one or more of metal oxides, metal nitrides, silicates, diatomaceous earth, and diatomaceous earth modified by a silane coupling agent.
2. The fluorine-free flame retardant masterbatch according to claim 1, characterized in that: The siloxane copolymer PC resin A has a melt index of 15-35 g / 10 min, preferably 15-30 g / 10 min, and more preferably 15-25 g / 10 min, under the test conditions of 300° C. and 1.2 kg; Preferably, in the siloxane copolymer PC resin A, the mass content of the siloxane copolymer unit is 4-10%, preferably 4-9%, more preferably 5-9%.
3. The fluorine-free flame retardant masterbatch according to claim 1 or 2, characterized in that: The porous material is diatomaceous earth modified by a silane coupling agent, wherein the mass ratio of the silane coupling agent to the diatomaceous earth is 1:(2-9), preferably 1:(2-8), and more preferably 1:(2-7.5); Preferably, the silane coupling agent in the silane coupling agent-modified diatomaceous earth is selected from one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.
4. A method for preparing a fluorine-free flame retardant masterbatch according to any one of claims 1 to 3, characterized in that: The following steps are involved: After fully mixing the siloxane copolymer PC resin A, polyborosiloxane, porous material, antioxidant and lubricant, extruding and granulating, a fluorine-free flame retardant masterbatch is obtained; Preferably, the extrusion temperature is 245-270° C., and the extrusion speed is 100-200 rpm.
5. A polycarbonate composition, characterized in that Based on the total weight of 100%, it contains the following components: PC resin 68-90%, Siloxane copolymer PC resin B 6-20%, 1.5-18% of the fluorine-free flame retardant masterbatch in any one of claims 1-4, Antioxidant 0.2-0.6%, Lubricant 0.5-2%. Other additives 0-6%.
6. The polycarbonate composition according to claim 5, characterized in that The PC resin has a melt index of 3-65 g / 10 min, preferably 5-65 g / 10 min, and more preferably 5-50 g / 10 min, under the test conditions of 300° C. and 1.2 kg.
7. The polycarbonate composition according to claim 5 or 6, characterized in that: The siloxane copolymer PC resin B has a melt index of 0.1-5 g / 10 min, preferably 0.2-4 g / 10 min, and more preferably 0.2-3 g / 10 min under the test conditions of 300° C. and 1.2 kg; Preferably, in the siloxane copolymer PC resin B, the mass content of the siloxane copolymer unit is 12-35%, preferably 12-32%, more preferably 15-30%.
8. The polycarbonate composition according to any one of claims 5 to 7, characterized in that: The other auxiliary agents include any one or more of ultraviolet absorbers and toughening agents.
9. A method for preparing a polycarbonate composition according to any one of claims 5 to 8, characterized in that: The following steps are involved: The PC resin, the siloxane copolymerized PC resin B, the fluorine-free flame retardant masterbatch according to any one of claims 1 to 4, an antioxidant, a lubricant, and other additives are fully mixed, extruded, and pelletized to obtain a polycarbonate composition; Preferably, the extrusion temperature is 250-300° C., and the extrusion speed is 150-400 rpm.
10. Use of the polycarbonate composition according to any one of claims 5 to 8 in electronic appliances and outdoor photovoltaic equipment.
Citation Information
Patent Citations
High-transparent halogen-free flame-retarding scratch-resistant polycarbonate composite material and preparation method thereof
CN105670258A
Flame-retardant master batch and high-CTI flame-retardant PC product
CN116041871A
Halogen-free flame-retardant polycarbonate composition as well as preparation method and application thereof
CN116333475A
Polycarbonate resin composition and molded article thereof
JP2010270295A
Polycarbonate resin composition and formed product thereof
US20110245388A1